Sistem Kearsipan Elektronik dan Dampaknya terhadap Kinerja Pegawai: Studi Kasus di Sekretariat DPRD Provinsi Sumatera Selatan - Helda Fitriani; Holipah Holipah; Asmawati Asmawati (Badan Penerbit STIEPARI Press, 2025)
This study examines the implementation of the Electronic Archiving System and its impact on employee performance at the Secretariat Office of the Regional House of Representatives (DPRD) of South Sumatra Province. The background of the study is based on the increasing demand for efficiency and accountability in public institutions, where effective records management plays a strategic role in supporting administrative processes. A qualitative approach with a deductive method was employed to collect and analyze data through observations, interviews, document reviews, and literature studies. The research findings highlight that the application of the electronic archiving system, assessed through indicators such as hardware, software, application networks, and human resources, significantly contributes to improving employee performance. Employees demonstrated improvements in quality, quantity, time management, and collaboration in their daily work activities. Nevertheless, challenges were observed, particularly related to the limited mastery of the SRIKANDI application, data security risks, and the need for continuous technical training. Despite these obstacles, the electronic archiving system has generally enhanced efficiency and facilitated the management of official records. The study concludes that optimizing the system requires strengthening employee competencies, enhancing supervision, and integrating advanced technologies. Thus, the adoption of electronic archiving is not only beneficial for organizational memory preservation but also for promoting better performance and governance within public institutions.